Formation of [CoPt2Cl2(PPh3)4(μ 3-S)2] from facile heterometallation of [Pt2(PPh3)4(μ-S)2] and its facile deheterometallation via carbonylative desulfurization to give Pt-Pt bonded [Pt2(CO)2(PPh3)2(μ-S)] - Liu, H. (2014)
Journal of the Chemical Society - Dalton Transactions